Marital Violence Complainants and the Services Provided by a Women’s Police Station According to its Staff - Mirian Beccheri Cortez; Lídio Souza (Interação em Psicologia, 2016)
It was investigated the perceptions of a Women’s Police Station’s team about women complainants and the implications of their perception in evaluating everyday jobs they perform. Thematic Content Analysis were applied on individual interviews with 14 professional staff and generated the categories: “Poor woman” and “Rare cases” that characterizes women complainants and the more and less frequent denounces; “Why do they talk?” and “Why do other women keep silent?” aggregate material about the decision of report or not violence (fear, children, emotional and financial dependence, violence control). Dropouts process and recurrence of violence implicate on professional frustration, which seems to be favored also by perceptions about the women and on denunciation decisions. We highlight the importance of proper training and psychosocial support for these staff.